2019
DOI: 10.31186/j.agritropica.2.1.13-25
|View full text |Cite
|
Sign up to set email alerts
|

Alternatif Fortification Vitamin A for Lactating Mother Using Siomay Sauce Enriched with Red Palm Oil

Abstract: Siomay is a popular street foods in urban and rural areas of Indonesia. Due to its characteristics siomay sauce can be incorporated with RPO (RPO)  for vitamin A fortification.  The objective of the study were determining the effect of RPO addition to the characteristic of siomay sauce, and  determining the preference of siomay sauce added with various amount of RPO.  A four levels addition of RPO (0.0 g, 1.5 g, 3.0 g and 4.5 g) were added to siumay sauce. The physical characteristics  (viscosity, emulsion sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…This study is in line with research from various studies that preference for aroma decreases with more addition serving of RPOO in the product (Budiyanto et al, 2019a;Budiyanto et al, 2019b;Novita et al, 2020;Nurhayati dan Budiyanto, 2026;Robiyansyah et al, 2017). This is presumably because red palm oil has an unpleasant aroma.…”
Section: Aromasupporting
confidence: 90%
See 2 more Smart Citations
“…This study is in line with research from various studies that preference for aroma decreases with more addition serving of RPOO in the product (Budiyanto et al, 2019a;Budiyanto et al, 2019b;Novita et al, 2020;Nurhayati dan Budiyanto, 2026;Robiyansyah et al, 2017). This is presumably because red palm oil has an unpleasant aroma.…”
Section: Aromasupporting
confidence: 90%
“…In addition, the substitution of RPOO up to 75% in original oil in siamay sauce did not affect the preference of siomay (Budiyanto et al, 2019a).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…RPOO mengandung vitamin A, vitamin E, dan antioksidan yang sangat bermanfaat bagi tubuh. RPOO dapat disubstitusi pada produk pangan misalnya pada pembuatan saus bakso bakar, bumbu kacang batagor, bumbu siomay, bumbu mi ayam (Agustina et al, 2019;Budiyanto et al, 2019;Nofita et al, 2020;Yupita et al, 2022). Oleh karena itu, pada kegiatan pengabdian ini mengenai sosialisasi stunting dan sosialisasi gulai sari buah kelapa sawit dan lele yang mengandung vitamin A, vitamin E, dan protein sebagai makanan pencegah stunting.…”
Section: A Latar Belakangunclassified
“…Carotenoids are one of the key compounds highly retained after a special refining process and give red palm oil its orange-red color. Studies have shown that the amount of retained carotenoids after refining ranges from 500 to 786 parts per million depending on the condition of crude red palm oil before refining 16 . About 80 of the carotenoids retained were found to be consisted of 0.2 phytoene, 0.6 phytofluene, 41.3 α-carotene, 10.2…”
Section: Carotenoidsmentioning
confidence: 99%